Otomyiasis: Systematic Review - Rodríguez-Ruiz, María Teresa; Acosta, Ana María; Cifuentes-Cardozo, Eduardo; Chirveches, María Alejandra; Rosselli, Diego (International Archives of Otorhinolaryngology, 2019)
Introduction Myiasis is a disease caused by fly larvae that grow in the tissues of animals and humans. It can cause a variety of local symptoms, like erythema or pain, depending on its location, and generalized symptomatology, such as fever and malaise. Myiasis can generate severe complications, for instance sepsis, or directly impact vital tissues. Its management varies depending on the location, and on the preferences of the doctor that faces this challenge. Myiasis usually occurs in tropical countries, and, in many places, it is not a rare condition. The cases are rarely reported, and there are no published management protocols.Objective To review the literature regarding the most common agents, the predisposing factors and the treatment alternatives for otic myiasis, a rare form of human myiasis caused by the infestation of fly larvae in the ear cavities.Data synthesis We present a systematic review of the literature. The search in five databases (Medline, Embase, Cochrane Database of Systematic Reviews, LILACS and RedALyC) led to 63 published cases from 24 countries, in the 5 continents. The ages of the patients ranged from newborn to 65 years old. The most common agents belong to the Sarcophagidae or Calliphoridae families. Chronic otitis media, previous otic surgical procedures, mental deficit, alcohol or drug abuse, sleeping outdoors, prostration, and malnutrition were predisposing factors. The treatment alternatives are herein discussed.Conclusion The results highlight the need for monitoring, follow-up and standardization of medical approaches.
Keywords: diptera; ear diseases; larva; myiasis; parasites; sarcophagidae